Navigating Cultural Diversity in Early Childhood Classrooms: The Role of Habitus in Teacher-Child Interactions - Astuti, Sriyati Dwi; Lessy, Zulkipli; Sibawaihi, Sibawaihi (COUNS-EDU: The International Journal of Counseling and Education, 2025)
Early Childhood Education (ECE) plays a crucial role in introducing children to the values of cultural diversity through educator-child interactions, particularly within Indonesia’s multiethnic context, where risks of intercultural conflict persist. This study explores how harmonious interactions between educators and children are maintained in culturally diverse settings. Using a qualitative approach grounded in Pierre Bourdieu’s theory of habitus, the research involved 10 educators and 30 children at Fastrack Funschool Yogyakarta. Data were collected through interviews and classroom observations, using the Classroom Assessment Scoring System (CLASS) to evaluate the quality of interactions across three domains: Emotional Support, Classroom Organization, and Instructional Support. Scores ranged from 1 (low) to 7 (high), indicating the extent and quality of positive interaction indicators. The results show that educators at Fastrack Funschool embody culturally aware teaching practices that promote mutual respect and tolerance. These practices are reflected in warm emotional climates, effective classroom management, and supportive instructional strategies. Interactions are characterized by sensitivity to cultural differences, flexibility in accommodating children’s perspectives, and responsiveness to individual needs. Through consistent social practices, children internalize inclusive values, which contribute to forming a culturally sensitive habitus. The study concludes that high-quality educator-child interactions serve as a key mechanism for fostering cultural harmony, building a learning environment that is both inclusive and adaptive to Indonesia’s cultural plurality. These findings emphasize the transformative potential of ECE settings in promoting intercultural understanding and shaping children’s social dispositions for living in a diverse society.